Moulding parameter optimisation for the best sintered density - Jamaludin, Khairur Rijal; Muhamad, Norhamidi; Ab. Rahman, Mohd. Nizam; M. Amin, Sri Yulis; Ahmad, Sufizar; Ibrahim, Mohd. Halim Irwan; Murtadhahadi, Murtadhahadi; Mohamad Nor, Nor Hafiez (International Association of Engineers, 2009)
Injection moulding parameters that simultaneously satisfy green part qualities (green defect, green strength and green density) have been optimised using L27 (313) Taguchi orthogonal array. Moulding variables involved in the optimisation are the moulding pressure, moulding temperature, mould temperature, holding pressure, moulding rate, holding time and cooling time. The analysis of variance (ANOVA) is employed to determine the significant levels (a) and contributions of the variables to the green qualities. Results show that the mould temperature and holding time is highly significant simultaneously to the green qualities, while the holding pressure and cooling time does not show any significance. Besides that, densification of the compact moulded with the optimised moulding parameter is presented in this paper. With sintering temperature ranging from 1340 to 1400 Â°C while heating rate and dwell time remains at 10 Â°C/min and 4 hours respectively demonstrates that the optimised moulding parameter is enabled to produce a sintered part with a density which is very close to the solid density of SS316L.